Regional patterns and associated factors of self-medication in Peru: analysis of a national survey - Pinedo Bardales, Maria; Rizo Patrón, Emiliana; Riveros, Maribel; E. Gonzales, Brayan E. (Horizonte Sanitario, 2026)
Objective. To assess the factors associated with self-medication across Peru’s macroregions using data from the National Health User Satisfaction Survey 2016 (ENSUSALUD 2016). Materials and methods. To assess the factors associated with self-medication across Peru’s macroregions using data from the National Health User Satisfaction Survey 2016 (ENSUSALUD 2016).Results. Self-medication was most frequent in the Eastern macroregion (82.3%). In the Northern macroregion, lower prevalence was associated with having secondary (aPR: 0.83) or higher education (aPR: 0.80), affiliation with the Comprehensive Health Insurance (aPR: 0.85) or EsSalud (aPR: 0.86), purchasing antibiotics (aPR: 0.80) and knowledge of the duration of the treatment (aPR: 0.52-0.54). Higher prevalence of self-medication was associated with having private insurance (aPR: 1.21), being convalescent, retired or a domestic worker (aPR: 1.91), and knowledge of drug dosage (aPR: 4.50-4.78). Conclusions. Regional variations were identified across the Central, Southern, Eastern and Lima Metropolitana macroregions, associated with sociodemographic and knowledge differences. These findings highlight the need to implement region-specific interventions to promote safe and rational medicine use. Keywords: Self-medication; Associated factors; Prescription; Peru; Antibiotics